Appropriate postharvest management to reduce losses of vegetables in the royal project foundation - D. Boonyakiat (2018)
Appropriate postharvest management to reduce losses of vegetables in the Royal Project Foundation was conducted by surveying and gathering information on supply chain of five vegetables, namely pointed cabbage, baby Chinese cabbages (pak-choi), bi-colored sweet corn, chayote shoot and Japanese cucumber. Postharvest losses of vegetables were determined at each stage of the supply chain starting from Chiang Mai province through Bangkok; in the field after harvesting, at the Development Center packhouse, at Chiang Mai packhouse, at Bangkok packhouse and at the Royal Project retail shop in Bangkok. The results showed that for pointed cabbage, Chinese cabbage, sweet corn postharvest losses were 63.79, 59.14 and 3.85%, respectively. Postharvest losses of chayote shoot were 39.37%, which were mainly due to wilting. The main factor contributing to losses of Japanese cucumber (59.11%) was due to produce not meeting the required market standard. After applying appropriate postharvest management, for example, temperature control, hygienic cleaning, using active packaging and reducing the duration of the supply chain, postharvest losses of all vegetables were remarkably reduced.